The Effect of Inflation on Capital Adequacy in Iraqi Banking Sector with Statistical Analysis - Ahmed Mohammed Ahmed; Dr.Rasha Ghayad; Dr.Elham Abdulkreem Hussain (Migration Letters, 2023)
The study investigates the correlation between specific economic variables (inflation) and the financial performance of government-owned banks in Iraq from 2000 to 2021. It aims to determine the impact and relationships of that variable on capital adequacy ratios. Where it was found that there is a statistically significant correlation and effect between inflation and capital adequacy. The research employs statistical tools like SPSS and MATLAB for data analysis and modeling to explore the logical connections between the variables. By focusing on these variables, the study aims to provide insights into the banking sector’s performance.